Prognostic value of carbohydrate antigen 125 combined with N-terminal pro B-type natriuretic peptide in patients with acute heart failure: a prospective cohort study in Vietnam - Chau Minh Truong; Nguyen Hoang Nguyen Do; Hoa Ngoc Chau; Truc Thanh Thai (BMC Cardiovascular Disorders)
Abstract Background Carbohydrate antigen 125 (CA125) is an emerging prognostic biomarker for acute heart failure (AHF). This study aimed to evaluate the prognostic utility of CA125 in combination with N-terminal pro–B-type natriuretic peptide (NT-proBNP) for predicting cardiovascular mortality, all-cause mortality, and a composite outcome of all-cause mortality or rehospitalization due to heart failure in patients with AHF. Methods This prospective observational study included 316 patients with AHF. Both CA125 and NT-proBNP levels were measured at the time of first admission. Mortality and rehospitalization due to heart failure were recorded over a 12-month follow-up period. Results During the follow-up period, 38 patients (12.0%) died from cardiovascular disease, 81 patients (25.6%) died from any cause, and 145 patients (45.9%) experienced either all-cause mortality or rehospitalization due to heart failure. In multivariate Cox regression analyses, the combination of high CA125 and high NT-proBNP levels was associated with increased risks of cardiovascular mortality (adjusted Hazard Ratio [aHR] = 11.77, 95% Confidence Interval [CI]: 3.73–37.09, p < 0.001), all-cause mortality (aHR = 4.53, 95% CI: 1.99–10.28, p < 0.001), and the composite outcome (aHR = 6.02, 95% CI: 2.75–13.24, p < 0.001). The addition of CA125 significantly improved prognostic performance when combined with NT-proBNP. Conclusions Both CA125 and NT-proBNP are significant prognostic biomarkers in patients with AHF. The combination of CA125 and NT-proBNP significantly enhances the prediction of cardiovascular mortality, all-cause mortality and the composite outcome of all-cause mortality or rehospitalization due to heart failure in patients with AHF.